Analysis of the Application of Islamic Business Ethics Values in Shari`Ah Hotels in the City - Marini Marini; Rapi Rapi; Dharma Setiawan (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
The main purpose of this study is to determine the ethical values of Islamic business that have been applied to sharia hotels in Bengkulu City, and to find out whether Syari`ah Hotels in Bengkulu City have followed the Minister of Tourism and Creative Economy Regulation No. 2 of 2014 regarding guidelines for the implementation of Sharia Hotels. This type of research is a qualitative approach. The method used in this research is descriptive method. The population in this study were all managers and employees of sharia hotels in Bengkulu City. Based on research on the Analysis of the Application of Islamic Business Ethical Values at Syari`a Hotels in Bengkulu City, it can be concluded that sharia hotels in Bengkulu City have implemented Islamic business ethics principles, such as Unity (Tawhid/unity), Balance ( Equilibrium/fair), Free Will (Free Will), Responsibility (Responsibility), Truth (Truth, Goodnes, Honesty). However, from the aspect of products, services and management, they have not fully followed the Regulation of the Minister of Tourism and Creative Economy No. 2 of 2014, there are still aspects that have not been fulfilled, as evidenced by the fact that they have not received a Sharia Hotel Business certificate from the National Sharia Council of the Indonesian Ulema Council.